ACTR-30. UPDATED EFFICACY AND SAFETY OF DABRAFENIB PLUS TRAMETINIB IN PATIENTS WITH RECURRENT/REFRACTORY BRAF V600E–MUTATED HIGH-GRADE GLIOMA (HGG) AND LOW-GRADE GLIOMA (LGG). (11th November 2019) - Wen, Patrick; Stein, Alexander; van den Bent, Martin; De Greve, Jacques; Dietrich, Sascha; De Vos, Filip; von Bubnoff, Nikolas; van Linde, Myra; Lai, Albert; Prager, Gerald; Campone, Mario; Fasolo, Angelica; et al.
Abstract: BACKGROUND: There is a lack of treatment options for HGG and LGG patients. BRAF V600E mutations are uncommon in glioma, with a poor long-term prognosis. Combined BRAF/MEK inhibition extends progression-free survival (PFS) and overall survival (OS) in BRAF V600E–mutated melanoma, non small-cell lung cancer, and anaplastic thyroid cancer. METHODS: This phase 2, open-label trial (NCT02034110) evaluated dabrafenib (BRAF inhibitor, 150mg BID) plus trametinib (MEK inhibitor, 2mg QD) in patients with BRAF V600E mutations in 9 rare tumor types, including HGG and LGG. Eligible patients had histologically-confirmed recurrent or progressive glioma (LGG:WHO grade 1 or 2; HGG:WHO grade 3 or 4), with HGG patients required to have received radiotherapy and first-line chemotherapy, or concurrent chemoradiation. Treatment continued until unacceptable toxicity, disease progression, or death. Primary endpoint was investigator-assessed objective response rate (ORR) using RANO criteria. Secondary endpoints included duration of response (DOR), PFS, OS, and safety. RESULTS: Interim analysis (IA) #14 (data cutoff: April 2, 2018) reported additional 3 months follow-up, with 49 patients enrolled (HGG, n=39; LGG, n=10) and 3 patients not evaluable for response. In HGG patients, ORR was 27% (10/37; 95%CI: 13.8%-44.1%), including CR (n=1), PR (n=9), and SD (n=11), with 16 patients currently ongoing treatment. In LGG patients, ORR was 56% (5/9; 95%CI: 26.8%-79.3%), including PR (n=5) and SD (n=4), with 6 patients currently ongoing treatment. OS, PFS, and DOR will be presented (IA#15). In HGG patients, adverse events (AEs) included fatigue (33%), headache (31%), rash (28%), and pyrexia (23%); grade 3/4 AEs included neutropenia (8%) and fatigue (5%). In LGG patients, AEs included headache (70%), fatigue, pyrexia (60% each), nausea, and arthralgia (50% each); grade 3/4 AEs included fatigue (20%). CONCLUSIONS: Dabrafenib plus trametinib demonstrated promising efficacy in patients with recurrent or refractory BRAF V600E‒mutated HGG or LGG, with manageable AEs and no new safety signals.